Cognitive Outcome of Intracerebral Hemorrhage Patients with and without Pneumonia - Carissa Vania Pratama; Cep Juli; Chandra Calista; Suryani Gunadharma; Yusuf Wibisono; Paulus Anam Ong (Althea Medical Journal, 2022)
Background: There are high prevalence of cognitive impairment in patients with intracerebral hemorrhage (ICH) that may worsen the patients’ outcomes. Pneumonia, as the significant infection complication in stroke patients, may aggravate the decline in the cognitive outcome of patients. This study aimed to explore the cognitive outcomes among patients with or without pneumonia among patients with intracerebral hemorrhage.Methods: A cross-sectional retrospective analytical comparative numeric study was conducted from September 2020 to February 2021, using secondary data of patients with intracerebral hemorrhage admitted to the Department of Neurology Dr. Hasan Sadikin General Hospital in the year 2019. A total sampling method was employed. Data on pneumonia in stroke patients was retrieved, consisting of patients with pneumonia and without pneumonia. Data on Mini-Mental State Examination (MMSE) scores as the measures of cognitive outcomes were compared using the Mann-Whitney U test.Results: There were 108 patients with intracerebral hemorrhage included. There was a statistically significant difference (p value 0.049) in MMSE scores with  median MMSE score for pneumonia patients (n = 27) and non-pneumonia patients (n = 81) were 25 and 21, respectively.Conclusions: Cognitive outcome is worse in patients with pneumonia than those without pneumonia. Early intervention is needed for intracerebral hemorrhage patients who develop pneumonia as a complication to improve the cognitive outcome.